2020
DOI: 10.21776/ub.rjls.2020.007.03.7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Bottom Sediment in Lekok Water, Pasuruan Regency, East Java

Abstract: Lekok water is one of the open waters. This will greatly affect the sedimentation process in Lekok water. The purpose of this study is to examine the distribution of bottom sediments in Lekok Water, Pasuruan Regency. The study was conducted in October-November 2019 using ekman grab at 9 site points. Sediment samples were obtained then analyzed in the laboratory to determine the grain size, as well as statistical calculations to analyze the distribution of the sediment. Based on the results of the study note th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The viscosity, syneresis, and rehydration values of instant rowe luwa porridge increase with increased temperature. This is in line with what has been reported by Muchlisyiyah et al (2020), Puspitowati & Driscoll (2007), and Denchai et al (2019) that the level of viscosity, synthesis, and rehydration increased with pre-gelatinization temperature.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 93%
See 1 more Smart Citation
“…The viscosity, syneresis, and rehydration values of instant rowe luwa porridge increase with increased temperature. This is in line with what has been reported by Muchlisyiyah et al (2020), Puspitowati & Driscoll (2007), and Denchai et al (2019) that the level of viscosity, synthesis, and rehydration increased with pre-gelatinization temperature.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 93%
“…Furthermore, it undergoes gelatinization and results in increased viscosity. Muchlisyiyah et al (2020) reported that increase time and temperature have increased gel consistency. Pre-gelatinization has increased the thickness of red glutinous rice flour.…”
Section: Viscositymentioning
confidence: 99%